Pendekatan Komunitas dan Motivasi Mahasiswa Memutuskan Kuliah di STIT QA - Yoyo Yoyo (J-STAF : Siddiq, Tabligh, Amanah, Fathonah, 2022)
The purpose of writing this article is to find out about the brand community approach andthe motivation for choosing a campus as a place to study at STIT QA. The writing of thisarticleuses qualitative methods with a case study approach and a literature study. A casestudy is a model that focuses on exploring one particular case or several cases in detail byextracting in-depth data. Various sources of information that are rich in context are usedfor data mining. From the discussion, it can be concluded that STIT QA as a relatively newinstitution is required to make acceleration and accuracy in regulating its educationalmarketing strategy in order to fulfill the wishes of the stakeholders. Among the things thatneed attention are how to develop a brand community approach as an agency, as a sourceof information, and as a collective interaction. In addition, a basic understanding of thecommunity's motivational factors is needed, in this case students choose this institution tostudy.